OVERVIEW OF TUBERCULOSIS SURVEILLANCE STAGES AT THE OEBOBO COMMUNITY HEALTH CENTER - Wahyuni, Maria Magdalena Dwi; Landi, Soleman; Ardiansyah, Dimas Rohman; Lewar, Benedicta Sabu; Kadek, Triya Tabita; Adu, Petronela Adelfin; Mau, Yohana; Azizah, Nur Asma (JURNAL WIDYA MEDIKA, 2026)
Tuberculosis (TB) remains a serious public health challenge in Indonesia, placing community health centers at the forefront of epidemiological surveillance. This qualitative study, utilizing a descriptive thematic analysis design, was conducted from October to November 2025 to evaluate the TB surveillance stages, case-finding mechanisms, and the internal strengths and weaknesses of the Oebobo Community Health Center. Data were collected from 12 informants, comprising TB program management, the surveillance team, and 10 TB patients, through in-depth and structured interviews, supplemented by a review of monthly health center reports. The findings indicate that while the surveillance stages (collection, processing, analysis, interpretation, and dissemination) are systematically implemented, case-finding relies heavily on contact investigation, active screening, and the optimization of TB cadres. The primary strengths of the program include its proactive, community-based approach and the use of periodic data analysis to guide interventions. However, the lack of adequate laboratory facilities for diagnosis remains a significant barrier. Ultimately, while TB surveillance at the Oebobo Community Health Center is operational and well-integrated into the community, it is not yet fully effective due to these infrastructure limitations.